COVID-19 transport restrictions in Ireland: impact on air quality and respiratory hospital admissions. (September 2021) - Quintyne, K.I.; Kelly, C.; Sheridan, A.; Kenny, P.; O'Dwyer, M.
Abstract: Aim: Exposure to poor air quality is a well-established factor for exacerbation of respiratory system diseases (RSDs); whether air pollutants are a cause of the development of RSD, however, remains unclear. This study aimed to examine the relationship between COVID-19 transport restrictions and hospital admissions because of RSD in Dublin city and county for 2020. Study design: This was a retrospective population-based cohort. Methods: Admission data were collected from the Health Service Executive Hospital In-patient Enquiry. Daily count of hospital admissions with Dublin city and county address with primary diagnosis of RSD was performed. The daily air nitrogen dioxide (NO2 ) data were obtained from the Environmental Protection Agency (EPA). Results: During the period of transport restrictions, there was a reduction in the annual mean NO2 from 25 μg/m 3 to 17 μg/m 3 ( P < 0.001), and decreases in hospital admissions for RSD were observed. Among the 9934 patient episodes included in this study, the mean age at admission was 61.5 years, 57.8% were female (n = 5744), and mean (standard deviation) length of stay was 7.5 (13.52) days. Conclusion: This study, using routinely gathered data, suggests that decreases in ambient NO2 as related to COVID-19 transport restrictions were significantly associated with lower asthma and chronic obstructive pulmonary disease admissions.